Loyalitas konsumen bagi bauran pemasaran pada usaha warung - Ariba, Nadia (Maliki Interdisciplinary Journal, 2023)
Companies or entrepreneurs definitely want their business to be successful. To achieve success, there needs to be an effort to promote the product well. Apart from that, marketing skills and product knowledge are required. Apart from skills, public relations is needed as a management function to achieve success. Among the marketing mix discussed in this research are price and place. These are the things that influence consumer loyalty, which has a big influence on business success. This was proven through observation activities carried out at Warung Koneng. The results of these observations show that price and place influence service quality which has a positive impact on consumer loyalty.